1937
DOI: 10.1084/jem.65.3.373
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphatics and Lymph Flow in the Edematous Skin of Human Beings With Cardiac and Renal Disease

Abstract: Local intradermal injections of dye have disclosed the fact that the skin lymphatics in regions of cardiac edema are patent, full of fluid and much widened. Intercommunication between them is ready and dye escapes from them more rapidly than from the vessels of normal skin. A retrograde distribution of dye by way of the lymphatics often occurs and it may pass unseen along the deeper channels to emerge in the skin at unexpected, distant situations. A valvular incompetence of the lymphatics consequent on dilatat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1937
1937
1960
1960

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 7 publications
2
28
0
1
Order By: Relevance
“…of an isotonic 11 per cent aqueous solution of an innocuous vital dye, patent blue V 1 (1,2). 0.1 cc.…”
Section: Methods and Preliminary Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…of an isotonic 11 per cent aqueous solution of an innocuous vital dye, patent blue V 1 (1,2). 0.1 cc.…”
Section: Methods and Preliminary Experimentsmentioning
confidence: 99%
“…(Received for publication, March 9, 1937) Previous papers from this laboratory have shown that every intradermal injection is truly intralymphatic (1)(2)(3). Dyes introduced in this way enter the superficial plexus of lymphatics through channels torn by the needle; and particulate substances which are punctured, scratched or even "vaccinated" into the skin pass in some part directly into these channels and are carried to the regional nodes (4,5).…”
Section: (From the Laboratories Of The Rockefeller Institute For Medimentioning
confidence: 99%
“…Doubtless because of the fact that lymphatic capillaries, unlike blood capillaries, are not readily visible under the microscope, no direct measurements of the lymph pressure in lymphatic capillaries of the skin have been reported previously. However, in the course of other studies (10)(11)(12)(13)(14)(15) from this laboratory, the difficulty had been overcome by the development of methods whereby the lymphatic capillaries are rendered visible as they pass through uninjured living skin. As a result, all that was lacking for the study of the pressure relationships inside the lymphatic capillaries and round about them was a suitable method for the measurement of fluid pressure in these channels.…”
Section: Techniquesmentioning
confidence: 99%
“…Unfortunately visualization of the lymphatics did not always take place under the circumstances outlined. For this reason another technique was frequently used: a modification of one already described in many previous papers (10)(11)(12)(13)(14)(15)(16). Mice were anesthetized with nembutal, their ears were spread on porcelain plaques, and under the binocular microscope the skin of the ear was punctured with an especially sharp micro cannula, attached to the apparatus that had been filled with the solution containing vital red.…”
Section: The Determination Of Pressurementioning
confidence: 99%
See 1 more Smart Citation